Pemanfaatan Sampah Plastik Pet dan Kertas Sebagai Substitusi Agregat pada Beton Ringan pada Kolom Praktis Bangunan - Muhammad Bima Vladimir; Sahrah Umara Dewi; Riza Susanti; Puji Widodo (Universitas Diponegoro, 2023)
Almost all building construction projects use concrete as the material. The dead load of a construction building is affected by the specific gravity of the concrete. Lightweight concrete has a unit weight below 1900 kg/m3 (SNI 03-2847-2002). Lightweight concrete uses lightweight aggregate as a constituent, so PET plastic and paper can be used as aggregate substitutes. PET plastic has the characteristics of being durable, strong, light, thick, and with good abrasion resistance, which has a positive effect on the compressive strength test. The paper contains hydrogen, which can bind to OH molecules resulting in a stiff, stable, and strong bond. When the water evaporates, small voids filled with air will form, causing the concrete to become lighter. Based on this, an innovation emerged: the manufacture of lightweight concrete that utilizes PET and paper plastic waste. The study aimed to utilize PET and paper plastic waste as an aggregate substitute for lightweight concrete in practical building columns. This study will use experimental methods with variations in paper waste of 0% and 4% and variations in PET plastic waste of 0% and 0.2%. Cylindrical specimens measuring 15 cm x 30 cm were tested for compressive strength at seven days and 28 days of concrete and absorption at 28 days of concrete. The results of this study are that PET and paper plastic waste can be used as an aggregate substitute for lightweight concrete for practical columns and can achieve concrete compressive strength exceeding the K-125 plan by using SNI 7394:2008 as a reference for Job Mix Design.